2021
DOI: 10.1038/s41598-021-91144-z
|View full text |Cite
|
Sign up to set email alerts
|

Detecting pelvic fracture on 3D-CT using deep convolutional neural networks with multi-orientated slab images

Abstract: Pelvic fracture is one of the leading causes of death in the elderly, carrying a high risk of death within 1 year of fracture. This study proposes an automated method to detect pelvic fractures on 3-dimensional computed tomography (3D-CT). Deep convolutional neural networks (DCNNs) have been used for lesion detection on 2D and 3D medical images. However, training a DCNN directly using 3D images is complicated, computationally costly, and requires large amounts of training data. We propose a method that evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Additionally, these authors examined whether a CNN model could achieve accurate anatomical localization (right 1st–12th and left 1st–12th ribs) and classification (fresh, healing, and old fractures) of rib fractures, and showed that the sensitivity reached 0.971 and 0.949 on the right and left ribs, respectively 20 . Ukai et al 17 proposed an automated method to detect pelvic fractures in the 3D fracture region obtained by integrating multiple 2D fracture candidates, and reported that sensitivity was 0.805 and precision was 0.907. The ability of the CNN model in our study to automatically localize and classify fractures in whole-body CT axis slices of pelvic, rib, and spine fractures was comparable to that of previous CT studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, these authors examined whether a CNN model could achieve accurate anatomical localization (right 1st–12th and left 1st–12th ribs) and classification (fresh, healing, and old fractures) of rib fractures, and showed that the sensitivity reached 0.971 and 0.949 on the right and left ribs, respectively 20 . Ukai et al 17 proposed an automated method to detect pelvic fractures in the 3D fracture region obtained by integrating multiple 2D fracture candidates, and reported that sensitivity was 0.805 and precision was 0.907. The ability of the CNN model in our study to automatically localize and classify fractures in whole-body CT axis slices of pelvic, rib, and spine fractures was comparable to that of previous CT studies.…”
Section: Discussionmentioning
confidence: 99%
“…New CNN algorithms reduce human workload and can extract features that are difficult for humans to recognize. Some studies have reported fracture identification using CNN on radiographs and CT scans 15 17 . However, to our knowledge, automatic localization and classification of fractures in CT using CNN methods have only been reported for rib and pelvic fractures and each model can detect only a single type of fracture 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Surface fractures may not be seen in raw images. 44 These fracture properties and their combinations properly depict surface fatigue. 43 In practice, the time-consuming magnetic particle imaging (MPI) inspection approach does not apply to lowautomation railway infrastructure.…”
Section: Comparative Aspects Of the Current Studymentioning
confidence: 99%
“…The scans were preprocessed using image processing algorithms to identify characteristics similar to surface cracks. Surface fractures may not be seen in raw images 44 . These fracture properties and their combinations properly depict surface fatigue 43 .…”
Section: Introductionmentioning
confidence: 99%
“…All seventeen studies used a CNN to detect and /or classify fractures on CT scans [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Eight studies addressed detection of rib fractures [13,17,19,20,22,[25][26][27], three studies the performance for detection [12,21] and classification [18] of pelvic fractures, four for detection of spine fractures [14,16,23,28], one for detection and classification of femur fractures [24] and one of calcaneal fractures [15]. Fourteen studies used two output classes (fracture yes/no).…”
Section: Description Of Studiesmentioning
confidence: 99%